Improvement of Water Stability of Sand Admixed with Water-Soluble Organic Polymer - Changqing Qi; Yuxia Bai; Jin Liu; Zezhuo Song; Debi Prasanna Kanungo; Fan Bu; Qiongya Wang; Zhaojun Zeng (International Journal of Polymer Science)
Weak water stability of soil is one of the prime causes of soil erosion and slope damage. To understand the improvement on the water stability of sand by a soluble organic polymer (polyurethane, PU), we have conducted a series of water-stability and turbidity tests to evaluate the effects of different polymer content, densities, and immersion times. The mechanism of the improvements is investigated based on scanning electron and digital microscopes. Our results reveal that the polymer can effectively improve the water stability of sand, where the water-stability coefficient enhanced from zero to 100. The turbidity of the water after oscillation was determined, and its value reduced from 84.5 to 10 and kept stable, which further proved the PU improvement on the water stability of sand. The results can be considered as the reference for construction and management of riverbanks and drainage ditches.